Oral immunization of haemaggulutinin H5 expressed in plant endoplasmic reticulum with adjuvant saponin protects mice against highly pathogenic avian influenza A virus infection. Issue 1 (26th July 2014) - Lee, Goeun; Na, Yun Jeong; Yang, Bo‐Gie; Choi, Jun‐Pyo; Seo, Yong Bok; Hong, Chun‐Pyo; Yun, Chang Ho; Kim, Dae Heon; Sohn, Eun Ju; Kim, Jeong Hee; Sung, Young Chul; Kim, Yoon‐Keun; et al.
Summary Pandemics in poultry caused by the highly pathogenic avian influenza (HPAI) A virus occur too frequently globally, and there is growing concern about the HPAI A virus due to the possibility of a pandemic among humans. Thus, it is important to develop a vaccine against HPAI suitable for both humans and animals. Various approaches are underway to develop such vaccines. In particular, an edible vaccine would be a convenient way to vaccinate poultry because of the behaviour of the animals. However, an edible vaccine is still not available. In this study, we developed a strategy of effective vaccination of mice by the oral administration of transgenic Arabidopsis plants (HA‐TG) expressing haemagglutinin (HA) in the endoplasmic reticulum (ER). Expression of HA in the ER resulted in its high‐level accumulation, N‐glycosylation, protection from proteolytic degradation and long‐term stability. Oral administration of HA‐TG with saponin elicited high levels of HA‐specific systemic IgG and mucosal IgA responses in mice, which resulted in protection against a lethal influenza virus infection with attenuated inflammatory symptoms. Based on these results, we propose that oral administration of freeze‐dried leaf powders from transgenic plants expressing HA in the ER together with saponin is an attractive strategy for vaccination against influenza A virus.